Improvement of Stress-Induced Changes Related To Mood and Cognitive Function in Healthy Young Adults Following Supplementation With Ajwa Dates - Abdullah, N.; Mokhtar, R. H.; Marwan, A; Noh, N. A. (Universiti Sains Islam Malaysia, 2024)
This study tested the effects of Ajwa dates supplementation on stress-induced changes to mood and cognitive functions in healthy young adults. 20 young adults were selected to receive seven dates per day for six weeks. Subjects completed measures of mood (POMS and DASS-21 questionnaires), and cognitive functions (simple reaction time, Stroop, n-back tests) before and after six weeks of supplementation: following an acute stressor task (Trier Social Stress test). Analysis of coronary risk and renal profiles were also done before and after six weeks of supplementation. Parameters related to mood including tension subscale in POMS, and stress subscale in DASS-21 significantly improved from baseline to week six. Significant improvements were also observed in the mean reaction time of Stroop, 1-back and 2-back tests after week six. There were no changes in coronary risk and renal profile after six weeks of supplementation. Our findings indicate that Ajwa dates supplementation has the potential to alleviate stress-induced changes in mood and cognitive functions in healthy young adults without adverse effect on renal functions.